Makna Simbolik Tradisi Mappanretasi Masyarakat Bugis Pantai Pagatan - Irawan, Andri; Khairussalam (Huma: Jurnal Sosiologi, 2025)
Mappanretasi is an annual tradition practiced by the Bugis community at Pagatan Beach, symbolizing respect for the sea and the harmony between humans and nature. This study explores the symbolic meanings embedded in Mappanretasi using a qualitative phenomenological approach. Data were collected through observation, in-depth interviews, and documentation in Kusan Hilir District, Tanah Bumbu Regency, and analyzed using Miles and Huberman’s model. Findings reveal that Mappanretasi is not merely a ritual, but a rich symbolic system. Offerings of four-colored sticky rice represent the elements of earth, water, fire, and air; a rooster and hen symbolize cosmic balance; while gold and eggs signify purity and abundance. The ritual also reflects belief in the ancestral figure Sawerigading as the guardian of the sea. Drawing on Émile Durkheim’s theory, these symbols reinforce social solidarity and express collective values. The sacred arises not from the objects themselves, but from communal recognition. As such, Mappanretasi maintains social cohesion and transmits cultural identity across generations. This study enriches the discourse in cultural sociology, particularly in maritime symbolism, and serves as a reference for cultural preservation and community education. Future research may compare similar coastal traditions to uncover broader patterns of symbolic expression in Indonesian maritime culture.